ANALISIS PENDAPATAN USAHATANI BAWANG MERAH DI DESA LENYEK KECAMATAN LUWUK UTARA KABUPATEN BANGGAI - Waldi Sadaruddin; Mahludin Baruwadi; Amelia Murtisari (Agrinesia: Jurnal Ilmiah Agribisnis, 2017)
This study aims to analyze: 1) Onion farming cost structure in Lenyek Village, Luwuk Utara District, Banggai Regency, 2) Onion farming income in Lenyek Village, Luwuk Utara Sub-district, Banggai District. The study was conducted in Lenyek Village, Luwuk Utara District, Banggai District from April to July 2017 with a sample of 37 farmers. Data analysis used is descriptive analysis and income analysis. The results showed that the cost structure of onion farming in Lenyek Village, Luwuk Utara Subdistrict, Banggai Regency consist of fixed cost and variable cost. Average number / farmer for fixed cost of Rp. 577,388.08 and average amount / hectare of Rp. 712.111.98. While the average / farmer for variable cost of Rp. 49.806.351.35 and has an average / hectare amount of Rp. 61,427,833.33 with total average cost / farmer of Rp. 50,383,739.45 and the total average cost / hectare is Rp. 62.139.945,32. The average income level / onion farmers in Lenyek Village, Luwuk Utara District, Banggai Regency is Rp. 71,427,071,37 and farmer's income with average / hectare is Rp. 88.093.388.02.